PENGARUH EMPATHY, RESPONSIBILITY, DAN TANGIBLES PELAYANAN SOSIAL TERHADAP KEPUASAN MASYARAKAT DI PALANG MERAH INDONESIA (PMI) SURAKARTA - Herri Supriyanto; Dewi Pujiani (Faculty of Social, Economics and Humanities, 2021)
The authors have a goal to determine the influence of empathy, responsibility, and tangible in public health services to public satisfaction in PMI Surakarta either partially or simultaneously. Hypothesis in this research were: suspected empathy, responsibility, and tangible in social service of public health have significant influence to satisfaction of society in PMI Surakarta either partially or simultaneously. Data needed in this research were primary data obtained by questionnaire method from sample counted 67 respondents. Data analysis used in this research were multiple linear regression test, t test, F test and coefficient of determination test. The result of data analysis in this research can be concluded that empathy, responsibility, and tangible in public health service have significant influence to the satisfaction of society in PMI Surakarta either partially or simultaneously.